Labor Mobility, Economic Shocks, and Jobless Growth : Evidence from Panel Data in Morocco - Verme, Paolo; Barry, Abdoul Gadiry; Guennouni, Jamal; Taamouti, Mohamed (World Bank, Washington, DC, 2014)
During the past 20 years, Morocco has implemented a wide range of macroeconomic, social, and labor market reforms that have delivered in terms of growth of gross domestic product and household welfare. Yet, these positive developments are not reflected by the main labor market indicators, a phenomenon observed elsewhere in developed and developing economies alike and labeled as "jobless growth." For the first time for Morocco, this paper uses quarterly panel data to investigate the question of labor mobility in an effort to determine whether people have moved to better sectors and jobs. The results point to significant labor mobility between labor statuses with quite distinct features across population groups. All groups experience some form of labor market mobility every quarter and women are as mobile as men. However, the transitions that women experience are very different from the transitions than men experience and women's performance is worse than men s performance in almost all aspects of labor mobility.